Fatores associados à ocorrência da violência de gênero - Silva, Bianka Sousa Martins (2014)
Objective: To assess factors related to the occurrence of gender violence in a population of northeastern Bahia in 2007 and identify risk behaviors in women who have witnessed family violence during their childhood and were victims of violence in adulthood. Methods: This was a cross-sectional study conducted with 4170 individuals, of both sexes, aged 15 years and living in the city of Feira de Santana , Bahia. A probabilistic sample of clusters derived from census tracts was used. Data were collected during home visits with use of household and individual questionnaire record. Bivariate and the Chi square test analyzes were performed considering IC95 % and p ≤ 0.05 for statistically significant association. To verify the factors associated with violence , we used a hierarchical logistic regression analysis. Results: The prevalence of physical and / or emotional violence was 18,63%. Regarding the history of violence in childhood prevalence was equal to 12,14%. Women had a higher prevalence (19,7%) than men (16,5%) with 1,31 times higher prevalence of victimization. It was observed that women who have never been to school (15,08%), non-white (12,61%) and had an income of up to 1 minimum wage (14.17%) had a higher incidence of physical violence in childhood. The women drinkers had 1,43 times higher prevalence of experiencing violence in childhood and, in relation to smoking, this prevalence increased to 1,56. Adjusted by hierarchical logistic regression analysis showed a positive association between women suffer physical and / or emotional violence with household type (RP = 1,28; IC95%: 1,10; 1,54), type of building (RP = 1,66; IC95%: 1,14; 2,41), smoking (RP = 1,36; IC95%: 1,10; 1,70) and violence in childhood (RP = 2,13; IC95%: 1,79; 2,53). Conclusions: Gender violence is a complex problem with social roots and that deserves to be addressed as a public health problem . Thus , it is urgent policies to combat poverty , interpersonal conflicts, especially those from the interior of the family system , substance use , particularly alcohol measures as well as preparation in the care of victims of violence and the deployment of a service to protect women victimized because many remain silent for fear of reprisals from their attackers.